Macromol. Chem. Phys. 3/2013. Issue 3 (5th February 2013) - Yagüe, Jose Luis; Coclite, Anna Maria; Petruczok, Christy; Gleason, Karen K.
<x xml:space="preserve">Abstract</x> Front Cover: Chemical vapor deposition (CVD) is a powerful technology for engineering surfaces. Initiated chemical vapor deposition (iCVD), a new technique utilizing benign reaction conditions to yield conformal and functional polymer thin films, is discussed along with the latest achievements in coating surfaces and 3D substrates with functional materials. The technique's use in biotechnology and selective permeation applications is reviewed, and future directions are discussed. Further details can be found in the article by J. L. Yagüe, A. M. Coclite, C. Petruczok, and K. K. Gleason* on page 302. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>